Involvement of Person with Disabilities (PWD) for Accessibility Tourism: A Case Study in Bukit Belungkor, Johor - Khalis Sharhana Zulkipli; Aqilah Awg Abd Rahman; Mohd Effendy Yusof (Enhanced Knowledge in Sciences and Technology, 2024)
This research addresses the imperative need for inclusivity in tourism by examining accessibility enhancement for individuals with sensory and physical disabilities in Bukit Belungkor, Johor. The methodology comprises a pilot hiking program tailored for individuals with disabilities or PWD (person with Disabilities) and stakeholder engagement, involving collaboration between diverse stakeholders such as local communities, government bodies, and tourism organizations. Then, a survey using questionnaire were followed post hiking programme towards the participants with disabilities with the help of volunteers. All data were analyzed by utilizing Excel, employing charts and diagrams to present visual insights into demographic patterns and knowledge levels on accessibility tourism in Bukit Belungkor. A 1-way NOVA is employed to analyze the Likert scale responses to assess the respondents’ preliminary assessments and perceptions on accessibility tourism aspects available in Bukit Belungkor. The study’s significance lies in its potential to contribute to inclusive and sustainable tourism practices for PWDs. Findings shed light on the current state of accessibility tourism in Bukit Belungkor and provide insights into challenges and opportunities for improvement. In conclusion, this research contributes to the discourse on accessibility tourism in Bukit Belungkor. Through the response of PWDs, this research aims to illuminate pathways toward a more inclusive tourism experience.